Pengaruh Kombinasi Diameter Pulley terhadap Uji Fungsi pada Mesin Bubut Multi Purpose Tipe HQ 400 - Sugiarto, Fikri Ariyadhana; Utama, Firman Yasa; Sakti, Arya Mahendra; Abdi, Ferly Isnomo (Jurnal Rekayasa Mesin, 2023)
Machine tools have a very important role in the industrial sector, especially the manufacturing industry. Various types of machine tools that are often used, one of which is a lathe. Damage that often occurs in the engine drive components, namely the pulley. Therefore, in this study, he was interested in conducting research entitled "The Effect of Pulley Diameter Combination on Functional Testing on the HQ 400 Type Multi-Purpose Lathe. Based on the results of the redesign on the HQ 400 multi-purpose machine, there is a redesigned component, namely the pulley. The dynamo machine used is the multi-purpose HQ 400 with a speed of 1500 RPM using a lathe/chisel eye that is used with a diameter of 6 mm and a 1 mm incision in the lathe function test, with the tested speed of 846.116 Rpm, 825.688 and Rpm, 307.649 Rpm on steel material of st 40 type steel with a length of 10 cm. from the test results on the function test of the hq 400 multi-purpose lathe, at speeds 1 and 2 there is a difference in time that is not too far, namely 25 seconds, while for speed 3 the lowest with the longest turning time is 9 minutes 35 seconds.